Aktivitas Komite Audit dan Dewan Direksi Independen terhadap Kinerja Keuangan pada Perusahaan yang terindeks LQ45 Periode 2017-2019 - Susi Sunanti; Nur Afridah; Andi Yulianto; Indah Dewi Mulyani; Hilda Kumala Wulandari (Universitas Muhadi Setiabudi, 2020)
Many previous studies have stated that financial performance such as the activities of the audit committee, independent board of directors can affect firm value. These results are confirmed by agency theory in financial performance in companies. The research also tries to prove again the confirmation of the previous or previous agency theory. This research was carried out on issuers of financial and banking institutions that were listed on the Indonesia Stock Exchange at the end of 2019, starting from the 2017 to 2019 research period. The sample used was purposive sampling technique, obtained 61 issuers as samples, then the data was analyzed by regression. multiple linear. The results of this study indicate that the activities of the audit committee and the board of directors of financial performance have an influence on the company's financial performance. This research can be said to be quite effective in working for the company, especially the sample in this study during the observation period. This is reflected by two of the three variables that have a significant effect on firm value as a reflection of the response to agency theory informed by the sample firms.